Gestión de las políticas públicas respecto al control, manejo, y protección de la fauna urbana y su incidencia en el centro histórico de la ciudad Latacunga - Fernández Álvarez, Ramiro Paul (2024)
In this research, the general objective was to analyze public policies regarding the management, protection and control of urban fauna and its incidence in the historic center of the city of Latacunga. The methodology used in the research was based on the mixed approach (qualitative and quantitative), using tools such as the questionnaire directed at 154 people who live in the historic center of the city and three properly structured interviews carried out with technical experts in the field. of the GADMCL, with the purpose of proposing alternatives with respect to the damage generated by urban fauna towards the heritage infrastructure, analyzing the correct application of the Ordinance that Regulates the Ownership, Management, Protection and Control of Urban Fauna in the Latacunga Canton added to This is the lack of an ordinance that cares for and protects the city's heritage infrastructure. It is concluded that Article 23 and Article 24 of the ordinance that protects urban fauna must be modified, in addition to the creation of an ordinance that protects the city's infrastructure, and the Pichincha Market must also be converted into a tourist market due to the strategic location in which it is located.